Interactive effect of 24-epibrassinolide and silicon on the alleviation of cadmium toxicity in rice (Oryza sativa L.) plants - Wang, Xueshun (Environmental technology, 2024)
Cadmium (Cd) pollution is a serious threat to food safety and human health. Minimization of Cd uptake and enhancing Cd tolerance in plants are vital to improve crop yield and reduce hazardous effects to humans. In this study, we investigate the effect of a synergistic system with phytohormone (24-Epibrassinolide, EBL) and silicon (Si) on Cd toxicity and accumulation of rice plants. The results revealed that Si, EBL and their combination rescued Cd-induced growth inhibition, as evidenced by the increased dry weight of root and shoot. The chlorophyll content and photosynthetic performance were improved. The activity of antioxidant enzymes (SOD, POD and CAT) was increased and oxidative stress was alleviated. More importantly, Cd content in root was decreased by 20.25%, 17.72% and 27.84%, while Cd content in shoot decreased by 21.17%, 16.47% and 25.88%, respectively. Moreover, Si, EBL and Si + EBL treatment enriched cell wall-bound Cd and reduced Cd toxicity to functional organelles. Meanwhile, the residual form of Cd was enriched and the highly toxic forms of Cd (inorganic and water-soluble Cd) were decreased. The joint application showed better effects than applying Si and EBL alone. Collectively, this study provides an effective way for Cd toxicity mitigation in rice plants